Current Population Status and Activity Pattern of Lesser Flamingos (Phoeniconaias minor) and Greater Flamingo (Phoenicopterus roseus) in Abijata-Shalla Lakes National Park (ASLNP), Ethiopia. (29th April 2014) - Kumssa, Tewodros; Bekele, Afework
Abstract : A study of the population status, habitat preference, and activity pattern of nonbreeding flamingos was carried out in Lakes Abijata, Shalla, and Chitu, part of the Great Rift Valley, Ethiopia, from 2011 to 2013. The current population status and habitat preference of flamingos in the area are still poorly known. Likewise, data on diurnal and seasonal activity pattern of the species are scarce and this leads to the misunderstanding of how Flamingos use local wetlands throughout the different seasons. Data regarding population size and activity pattern were gathered during the wet and dry seasons. Point-count method was used to estimate the population size. Behaviors were recorded using scan sampling techniques. A total of 53671 individuals representing two species of flamingo were counted during both wet and dry seasons from the three lakes. There were more flamingos during the dry season than the wet season in Lake Abijata contrary to Lakes Shalla and Chitu during the wet season. Lesser flamingos ( Phoeniconaias minor ) were the most abundant species comprising 95.39%, while Greater Flamingos ( Phoenicopterus roseus ) accounted for 4.61% of the total population. Lake Abijata is the major stronghold of Lesser Flamingos in the area. There was significant variation in the mean number of both species during the wet and dry season in the different study sites of the lake, respectively. The species were known to use varied habitats within the lakes. The Lesser Flamingo mainly preferred the shoreline and mudflat areas of the lakes. However, Greater Flamingo on several occasions showed preference to offshore area of the lakes. Seasonal average flock sizes were not similar between the species. There was a strong relationship between time allocated to each activity and time of day. Feeding activity varied among daylight hours and was higher in the evening (76.5%) and late morning (74.56%) and least during midday (54%). Some variations in activity breakdown were observed between time blocks and season. Conservation efforts in the park should include the wild flora and fauna not only of the land but also of the aquatic systems. The information in this study will be very useful for the future management of the species in the area.